Caught in the grey area between European Economic Community and European Federation? - Podhalicz, Mateusz (Vilnius University Open Series, 2020)
During the last decade of the EU history there has been an unprecedented increase of illiberal tendencies among certain EU Members – most notably Poland and Hungary, which in turn lead to violation of the values enshrined in Article 2 TEU. The present paper is brief attempt to determine whether the EU has any legal powers to confront rogue EU Members, which violate the rule of law and what these powers are.
Keywords: Solange doctrine; Reverse Solange doctrine; EU competences; rule of law; Article 7 of TEU